Cafés in the City Center: Flexible Workspaces and the Urban Balance of Life - Dian Duhita Permata; Himasari Hanan; Widiyani Widiyani (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2026)
The rise of flexible work styles in major cities has led to the emergence of alternative workspaces outside traditional office settings, including cafés, coworking spaces, and libraries. This study examines how café locations in city centres, when utilised as alternative work settings, can enhance work-life balance. The research employs a mixedmethods approach, combining spatial observation using Google Maps with a two-week tracking of respondents’ movements via Google Timeline. The findings reveal that most respondents prefer working in cafés situated in the city centre, particularly in areas such as Dago, Braga, Gasibu, and Buah Batu. Key factors influencing location preference include high accessibility, spatial proximity between functions, a diverse range of activities, and a visually appealing urban atmosphere. The study concludes that cafés in the city centre have evolved beyond their commercial function to become integral parts of the urban work-life environment, supporting both productivity and psychological well-being in contemporary urban life.